2020
DOI: 10.1021/acs.macromol.0c01221
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Behaviors of Hydrogels with Alternating Neutral/Highly Charged Sequences

Abstract: Polyelectrolyte gels comprising fixed ions exhibit swelling behaviors because of external solution conditions. Such behaviors are usually explained by using the Flory–Rehner model that considers the Donnan equilibrium. However, this model assumes a homogeneous distribution for fixed ions; therefore, its applicability to the case of heterogeneous distributions remains unclear. Here, we successfully designed a hydrogel with alternating neutral/highly charged sequences (i.e., tetrapoly­(acrylic acid)–poly­(ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(87 citation statements)
references
References 77 publications
3
83
1
Order By: Relevance
“…As indicated, the predictions clearly reproduce the swelling behaviors of the various Tetra-PAA-PEG gels under all external conditions examined, including the condition where the original FRGDM model fails. It is worth noting that the downward deviation at low-pH regions was attributed to the formation of the aggregation structure through hydrogen bonds between PAA and PEG, which was reported elsewhere as well [ 25 ]. This good correspondence indicates that the finite extensibility effect is essential for describing the elastic free energy of a highly swollen gel.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…As indicated, the predictions clearly reproduce the swelling behaviors of the various Tetra-PAA-PEG gels under all external conditions examined, including the condition where the original FRGDM model fails. It is worth noting that the downward deviation at low-pH regions was attributed to the formation of the aggregation structure through hydrogen bonds between PAA and PEG, which was reported elsewhere as well [ 25 ]. This good correspondence indicates that the finite extensibility effect is essential for describing the elastic free energy of a highly swollen gel.…”
Section: Resultssupporting
confidence: 60%
“…The network homogeneity in this gel was examined by spectroscopic and mechanical measurements, and it was found that the Tetra-PAA-PEG gel was a promising model for investigating the physicochemical properties of highly charged polyelectrolyte gels. In our previous study, we also investigated the swelling behaviors of the Tetra-PAA-PEG gel in various tuned external solutions, and validated the model describing the swelling behaviors of the Tetra-PAA-PEG gel through modification of the FRGD model with Manning’s counterion condensation model (i.e., the FRGDM model) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…When is 10 −4 M, the of the St-tetra-PEG gel with certain can be determined from the Donnan potential using Equation (14). Here, we additionally assume that γ is independent of , as in previous studies [ 16 , 21 , 32 ]. As should be inversely proportional to the swelling ratio Q , the of the St-tetra-PEG gel in the bath solution of any can be calculated by the following equation: …”
Section: Resultsmentioning
confidence: 99%
“…The other pressures of a charged gel, such as the pressure originating from electrostatic repulsion between the fixed ions, were also taken into account in the rigorous modeling of a charged gel, following some previous papers, which we assumed that such additional terms are excessively small to be ignorable relative to [ 16 , 17 ]. As the pressure of a charged gel should be balanced at its equilibrium swelling state, the equilibrium swelling state of charged gels can be expressed by Equation (1): is generally equal to its shear modulus, G [ 19 , 20 ], and can be determined from mechanical tests: follows the scaling relationship for the osmotic pressure of semidilute polymer solutions [ 21 ]: where is the polymer volume fraction, K is a parameter that depends on various factors such as the gel preparation conditions, and is the Flory exponent, which depends on the polymer–solvent affinity (0.5 for theta solvent and 0.588 for the athermal solvent). originates from the difference in the activity of the total mobile ions between the gel and the bath solution, , and is given by where k is the Boltzmann constant, T is the absolute temperature, and is the activity of the ion in the subsystem [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation